Spatiotemporal Clustering of Multidrug-Resistant and Extensively Drug-Resistant Tuberculosis Is Associated With Human Immunodeficiency Virus Status and Drug-Susceptibility Patterns in KwaZulu-Natal, South Africa. (20th September 2019) - Wolf, Allison; Padayatchi, Nesri; Naidoo, Kogieleum; Master, Iqbal; Mathema, Barun; O'Donnell, Max R
Abstract: Using an open-access spatiotemporal analytics program, we mapped spatiotemporal heterogeneity loci in tuberculosis (TB) cases (clusters) and dynamic changes, and characterized the drug-resistant TB clustering risk using routine microbiological data from KwaZulu-Natal, South Africa. The data may provide insight into transmission dynamics and support efficient deployment of public health resources.